Exploited fIShery resources of the Vembanad lake - Kurup, B Madhusoodana; Sebastian, M J; Sankaran, T M; Rabindranath, P (Indian Journal of Fisheries, 2011)
The Vembanad lake of Ketala (lat. 9Â°28 and 10Â°101’ and long. 76 Â°13’ and 76 Â°31’) is 60 km long from north to south (Cochin to Alleppey) and has an area of 21 OSO ha. Thanneermukkom salinity barrier has separated this lake into 2 entirely different ecosystems, estuarine northern sector or the downstream region (Cochin to Thanneermukkom; Cochin backwaters area, 12440 ha) and freshwater southern sector or the upstream region (Thanneermukkom to AUeppey; area, 8610 ha). So far no concerted attempt has been made to quantify the exploited fin fish and crustacean resources of this lake.